Analysis of the Influence of Motivational Factors and Barriers on Continuance Intention of Mobile Banking Usage in Indonesia - Jessica Tania; Arta Moro Sundjaja (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2026)
Mobile banking adoption in Indonesia has grown rapidly alongside increasing digital literacy. Yet, most prior studies have focused on initial adoption drivers, leaving a research gap in understanding the continuance intention (IU) of users who are already familiar with mobile banking. This study addresses that gap by applying Dual Factor Theory to analyze how Perceived Ease of Use (PU), Reward (RW), Risk Barrier (RB), and Image Barrier (IB) influence IU among Indonesian mobile banking users. Data were collected through an online questionnaire, and 300 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS‑SEM). The measurement model confirmed that all constructs were valid and reliable, with strong indicator loadings. The results show that motivational factors (PU and RW) have positive and significant effects on IU, whereas barrier factors (RB and IB) exhibit weaker or insignificant effects. These findings emphasize that in the post‑adoption stage, user motivation, particularly ease of use and incentives, is more dominant in sustaining continuance intention than barriers such as risk or negative image. This provides new insights compared to earlier studies that emphasized barriers as critical obstacles, demonstrating that in a mature digital environment like Indonesia, barriers lose relevance while motivational factors prevail. This research contributes theoretically by refining the application of Dual Factor Theory to the context of mobile banking continuance, showing that its effectiveness is stage-dependent. Practically, the study suggests that banks should prioritize enhancing usability and maintaining attractive reward programs to strengthen user loyalty, rather than focusing solely on reducing barriers.